Landscape 4. Landschaftsideen Nordeuropas und die visuelle Integrität von Stadt- und Kulturlandschaften im UNESCO-Welterbe. - Kloos, Michael (My University, 2015)
In der Arbeit werden die Hintergründe von "visueller Integrität" von Welterbestätten auf drei verschiedenen Ebenen untersucht: Politische Hintergründe der Integration von Landschaften als kulturellem Erbe in das Welterbeprogramm, eine detaillierte Fallstudie der jüngeren Diskussionen über die visuelle Integrität der Welterbe-Kulturlandschaft Oberes Mittelrheintal und der historische Hintergrund der Rezeption des Landschaftsbegriffs in Nordeuropa. Die Untersuchung zeigt, dass die Gründe für Fragen über die visuelle Integrität in komplexen Stadt- und Kulturlandschaften im UNESCO-Welterbe häufig auf Fehler zurückgeht, die während deren Nominierung gemacht wurden. Aufgrund der augenblicklichen Steigerung der Bedeutung kulturellen Erbes im Zusammenhang mit der wachsenden Bedeutung des Massentourismus für Städte und Regionen neigen "Insider" mit einer starken Beziehung zu lokalen Entscheidungsebenen dazu, Nominierungen für das Welterbe als eine Chance für eine erfolgreiche Stadt- und Regionalentwicklung zu sehen. Im Gegensatz hierzu stellen "Outsider" mit nationalem oder internationalem Entscheidungshintergrund häufig die Erhaltung solcher Stätten und deren Stadt- und Landschaftsbilder in den Vordergrund. Nominierungen von Stadt- und Kulturlandschaften für das Welterbe führen daher häufig zu widersprüchlichen Erwartungshaltungen auf unterschiedlichen Entscheidungsebenen. Vor diesem Hintergrund werden Empfehlungen für Nominierungsprozesse, das Management und das Konfliktmanagement in Welterbestätten erarbeitet. Diese Empfehlungen werden anhand von Fallstudien weiter ausgearbeitet. Daneben werden Empfehlungen für zukünftige Aktivitäten in der Grundlagenforschung und der angewandten Forschung erarbeitet.

In recent years, a relatively large number of World Heritage properties in Northern Europe, especially the ones located in the context of urban agglomerations, witnessed discussions about their visual integrity . Such discussions, referring to significant modifications of city images or landscape scenery (e.g. due to the erection of high-rise tower blocks or new infrastructural elements), appeared often in large-scale properties, the World Heritage Landscapes . In particular, the case of the Waldschlösschen Bridge, which led to a long, extremely emotional and somewhat painful debate and eventually to the deletion of the World Heritage property Dresden Elbe Valley from the UNESCO World Heritage List in 2009, triggered an extremely high public attention. The PhD thesis Landscape 4 investigates the background of such questions about the visual integrity of World Heritage properties on three different levels: The political background which led to the integration of landscapes as cultural heritage into the World Heritage programme, a detailed case study on the recent discussions about the visual Integrity of the World Heritage site Upper Middle Rhine Valley, and the historical background of the reception of the notion of landscape in Northern Europe. The investigation shows that the reasons for questions about the visual integrity of complex World Heritage properties on urban and regional scale very often do arise due to mistakes made during their nomination. In particular, stakeholders should be aware that inscription procedures of large-scale sites on the World Heritage List lead to very different expectations on various decision levels. Fuelled by the currently rising economical value of cultural heritage, especially due to the raising importance of mass tourism for cities and regions, insiders with a strong relationship to local decision levels tend to see World Heritage nominations as a chance for a successful economical development for cities and regions. In contrary, outsiders with a national and international background tend to stress the importance of the preservation and the conservation of such sites, their cityscapes and landscape scenery. As a result, the nomination of urban and cultural landscapes for the World Heritage List leads often to contradicting expectations on various decision levels. Against this background, the thesis provides recommendations concerning inscription processes, daily management and conflict management in Word Heritage properties. These recommendations are further elaborated in various case studies. Besides that, the PhD provides recommendations for future need in both fundamental and applied research.
Landscape 4. Landscape ideas in Northern Europe and the visual integrity of UNESCO World Heritage cultural and urban landscapes.
Keywords: Landschaft; Stadtlandschaft; Stadtbild; Landschaftsbild; Kulturlandschaft; Denkmalschutz; Entscheidungsprozess; Fallstudie; Leitfaden; Weltkulturerbe; Landschaftsbegriff; Unterschutzstellung; Nominierung